Framing scholars' perspectives of practices to address breaches of academic integrity in the Muslim world. Issue 4 (4th July 2022) - Akbar, Akbar; Carter, Carol; Sit, Helena; Picard, Michelle
ABSTRACT: Although previous work explained internal and external cultural challenges impacting academic integrity in the Muslim world, to date, no study has specifically examined the attempts and practices by the universities to address these challenges. The objective of this paper was to understand the actions taken by academics and institutions in the Muslim world to address, prevent breaches of academic integrity, and to recommend improvement of these practices. To capture institutional efforts and practices, relevant literature from 2010 to 2021 was reviewed to gather evidence of practices of academic integrity in higher education in the Muslim world. The findings suggest a framework that can be used for evaluation of current practices of academic integrity in the Muslim world, to go beyond plagiarism-focussed prevention, detection, and punishments.